2022
DOI: 10.1021/acs.joc.1c02908
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Copper-Catalyzed Intermolecular Cyanobenzoyldifluoromethylation of Alkenes: Access to Chiral β-Difluoroacyl Nitriles

Abstract: A novel asymmetric copper-catalyzed intermolecular cyanobenzoyldifluoromethylation of alkenes with iododifluoromethyl ketones and TMSCN has been reported, which provides a particularly valuable route to access chiral β-difluoroacyl nitriles with excellent enantioselectivities. The method permits the efficient cyanation of varied β-difluoroacyl-benzylic radicals in mild conditions with high functional group tolerance. The reaction proceeds through a radical pathway. In order to get insight into the stereochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Increasing or decreasing the amount of copper salt did not improve the yield of 3aa either (Table 1, entries 11 and 12). Additional control experiments confirmed that the copper catalyst, L1 and LPO are essential for this reaction (Table 1, entries [13][14][15].…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Increasing or decreasing the amount of copper salt did not improve the yield of 3aa either (Table 1, entries 11 and 12). Additional control experiments confirmed that the copper catalyst, L1 and LPO are essential for this reaction (Table 1, entries [13][14][15].…”
Section: Resultsmentioning
confidence: 84%
“…14 Very recently, our group disclosed a copper-catalyzed threecomponent reaction of iododifluoroacylated ketones, alkenes and trimethylsilonitrile (TMSCN) to afford β-difluoroacyl nitriles with excellent enantioselectivities. 15 Mechanistic exploration shows that in this reaction process, the copper catalyst first reacts with cyanide to form Cu II (CN) 2 species, which could then trap the radical intermediate generated from the addition of a fluoroalkyl radical to the CvC bond. However, the cyano-monofluoroalkylation of alkenes with valuable monofluoroalkyl reagents remains unexplored, but is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by our previous work, [11d] the reaction of 2‐iodo‐2,2‐difluoroacetophenones 1 a , styrene 2 a and TMSN 3 was chosen as a model reaction to optimize the reaction conditions. The reaction was conducted in anhydrous DME at room temperature with tert ‐butyl peroxybenzoate (TBPB) as the radical initiator, and catalyzed by Fe(OTf) 2 under nitrogen (Table 1, entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…[205] Shortly after, the enantioselective variant of the transformation was disclosed utilizing low loading of a CuÀ bisoxazoline complex and benzoylperoxide. [206] In most cases very good yields and enantioselectivities were reported.…”
Section: Carbofluoroalkylationsmentioning
confidence: 99%
“…Recently, Wu utilized a similar catalyst system for cyanofluoroalkylation of alkynes with iododfluoromethyl ketones [205] . Shortly after, the enantioselective variant of the transformation was disclosed utilizing low loading of a Cu−bisoxazoline complex and benzoylperoxide [206] . In most cases very good yields and enantioselectivities were reported.…”
Section: Multicomponent Reactionsmentioning
confidence: 99%